Rapid determination of methyl parathion in vegetables using electrochemical sensor fabricated from biomass-derived and β-cyclodextrin functionalized porous carbon spheres. (1st August 2022) - Li, Fang; Liu, Runqiang; Dubovyk, Volodymyr; Ran, Qiwen; Zhao, Hongyuan; Komarneni, Sridhar
Highlights: Porous carbon spheres (PCS) were prepared from sugarcane juice (SJ). SJPCS was modified with β-cyclodextrin (β-CD) to make a composite. SJPCS@β-CD/GCE sensor was fabricated for the detection of MP. SJPCS and β-CD have synergistic effect in enhancing the sensing performance. A low detection limit of 5.87 nM was achieved with the SJPCS@β-CD/GCE sensor. Abstract: Porous carbon spheres (PCS) derived from expired sugarcane juice (SJ) and modified with β-cyclodextrin (β-CD) were used for the fabrication of SJPCS@β-CD/GCE sensor with glassy carbon electrode (GCE) to detect methyl parathion (MP). SJPCS with interconnected porous structure exhibits excellent electrical conductivity, strong adsorption property, and high specific surface area, while β-CD with molecular recognition property achieves the uniform dispersion of SJPCS and promotes the recognition and adsorption of MP molecules. Thanks to the synergistic combination of SJPCS and β-CD, the SJPCS@β-CD/GCE sensor exhibited respectable MP determination performance with low limit of detection of 5.87 nM in the MP concentration range of 0.01–10 µM. For the MP detection in vegetables (onion, cabbage, spinach), the fabricated sensor showed good practicability with adequate relative standard deviation of 1.06% to 4.25% and satisfactory recoveries of 96.5 to 100.5%. A promising strategy for the rapid determination of methyl parathion in food products was developed.